Diagenesis of the Pennsylvanian –Lower Permian Copacabana Formation, western Bolivian Altiplano. (June 2020) - Nina, L.M.; Sial, A.N.; Barbosa, A.; Neumann, V.H.M.; Bark, G.; Garcia, R.; Wanhainen, C.; Blanco, M.
Abstract: This contribution presents the diagenetic evolution of limestone deposits in the Copacabana Formation that occurs in the northern Altiplano, in the Lake Titicaca area of western Bolivia. The best-exposed stratigraphic succession of the Copacabana Formation occurs in the Yampupata section, and its division into five facies successions is based on petrographic analysis, cathodoluminescence, x-ray fluorescence analysis (chemical composition) and stable isotope data (δ 18 O and δ 13 C). The results showed that the carbonate rocks experienced early marine diagenetic processes such as micritization during or after the deposition (eogenesis). The initial burial event (mesogenesis 1), characterized by stabilization of temperature-water carbonates by freshwater, and represented by bladed calcite-cement, equant calcite cement, dissolution, dolomitization, neomorphism, silicification and compaction (physical), occurred in shallow burial conditions. During the second burial episode (mesogenesis 2), in deeper burial environment the processes include: compaction (physical and chemical) and neomorphism. Diagenetic processes have affected reservoir quality in the Copacabana Formation during the mesodiagenesis, and reduced the conditions for development of high-quality conventional hydrocarbon reservoirs. Depleted O and C stable isotope signatures indicate that these carbonate rocks deposits underwent both meteoric and burial diagenesis including moderate water-rock interaction. Highlights: Copacabana Formation have experienced marine diagenetic processes such as the eogenesis, mesogenesis 1 and mesogenesis 2. Diagenetic processes affected reservoir quality, and limited the high-quality conventional hydrocarbon reservoirs. Depleted O and C stable isotope indicate that these carbonate rocks underwent both meteoric and burial diagenesis.